Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"– Provided by publisher.